PENGARUH KETERAMPILAN KOMUNIKASI INTERPERSONAL TERHADAP MOTIVASISISWA KELAS XI IPS SMA N 6 PONTIANAK - Murjani, Murjani; H. Matsum, Junaidi; Purwaningsih, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the effect of interpersonal communication skills to students learning motivation in class XI IPS SMA Negeri 6 Pontianak. This research was quantitative research with ex-postfacto research. The sample in this study was student of XI IPS SMA Negeri 6 Pontianak, totaling 86 students. The data were collected by using questionnaire has been test for validity and reliability. The techniques analysis data used normality test, linearity test, simple linear regression and hypothesis test with the SPSS version 16.0. The results of this study show the most students have social skills in the medium category. It wasproven that 12.79% students in low category, 77.90% students in the medium category, and 9.30% students in high category. The learning motivation of students in class XI IPS was mostly in the medium category shown from the percentage of research results, was 18.60% students in low category, 66.27% students in medium category, and 15.11% students in high category. This research have a positive influence between interpersonal communication skills to student learning motivation with a regression equation that was Y = 26.437 + 0.537X. The resultÂ of hypothesis test showing that the significant value (sig) of 0,000 is smaller than the level of significance (a) set at 0.05. It means that H0 was rejected and Ha was accepted. It can be concluded that interpersonal communication skills significantly influence to student learning motivation in Â class XI IPS SMA Negeri 6 Pontianak.Keywords: Interpersonal Communication Skills, Learning Motivation